Understanding Mental Health Policy Implementation Through Lived Experience of Professors in the Context of Graduate Student Supervision - Mooney, Jaclyne (Université d'Ottawa | University of Ottawa, 2024)
Over the past decade, Canadian university administrations have been grappling with establishing their role in providing mental health support to students on their campuses. This article describes a case study that applies sense-making theory and a life story methodology to professors’ lived experiences to understand how their knowledge and beliefs impact their perception of their role in supporting graduate student mental health. Schemas developed from four professors’ life stories provide insight into the impact that lived experience as a graduate student has on how professors’ make sense of their role. Two types of professor experiences emerged: a positive supervisor experience that the supervisor seeks to replicate, or the negative experience that the supervisor tries to repair through distancing themselves from the practices of their own graduate supervisor. In the absence of consistent and clear training on supervision and professor’s role in supporting graduate student mental health, the life stories of these four professors signal that lived experience of being a graduate student guides subsequent practice as a supervisor.
Keywords: mental health; graduate; supervision; framework; lived-experience; implementation; relationship